Smoking promotes vascular damage in apparently healthy men with low testosterone and increased subclinical inflammation. (3rd October 2022) - Ioakeimidis, N; Dima, I; Terentes-Printzios, D; Xydis, P; Angelis, A; Solomou, E; Gardikioti, V; Gourgouli, I; Papadatos, S; Kalfountzos, D; Tsioufis, C; Vlachopoulos, C
Abstract: Background: Testosterone deficiency and increased inflammation are both associated with an unfavourable vascular profile. Aim of the study was to examine whether smoking significantly deteriorates the effect of these pathophysiological mechanisms on arterial wall properties. Methods: Carotid intima media thickness (cIMT) and aortic pulse wave velocity (aPWV) were measured in 87 smokers and 112 aged-matched never smokers (mean age: 49±5 yrs) with no other cardiovascular (CV) risk factors/or manifest CV/atherosclerotic disease. Plasma total testosterone (TT) and high sensitivity reactive protein (hsCRP) levels were measured in the whole study population. Results: Both smokers and never smokers were divided into four subgroups according to measured low or normal TT levels (low TT<3.5 ng/ml) and high or low hsCRP levels. BMI and LDL-C levels were not different between the subgroups. In smokers the four TT/CRP subgroups had comparable cumulative tobacco smoke exposure. In smokers the low TT/high CRP subgroup had significantly higher aPWV and cIMT compared to the three other subgroups (P<0.01 and P<0.05, respectively by ANOVA, figures A-B) while in never smokers the four TT/CRP subgroups had comparable aPWV and cIMT (all P>0.05, figures C-D). The differences in aPWV and cIMT measurements between TT/CRP subgroups in smokers remained statistically significant after adjustment for age. Conclusions: The study shows that low TT combined with high CRP are associated with increased carotid IMT and aortic PWV in smokers with no other CV risk factors, while in never smokers the effect of combined low TT and high CRP concentration was not significant. Considering the predictive value of aortic stiffness and carotid thickness, the finding of this study imply interrelationships between tobacco cigarette smoke, subclinical inflammation and low testosterone level regarding changes in arterial wall properties. Funding Acknowledgement: Type of funding sources: None.